Islamisasi Konsep Pajak Menurut Syed M. Naquib Al-Attas - Sandy, Niken Baramurti Evieta Enggar; Junita, Sarina; Syaifuddin, Helmi (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
This study discusses the concept of tax Islamization according to Syed M. Naquib Al-Attas, where Al-Attas argues that tax Islamization aims to reform the taxation system to comply with sharia principles, which emphasize justice, social responsibility, and economic sustainability. Within the framework of Islamization, tax is not only seen as a fiscal instrument, but also as a spiritual and social means to achieve community welfare. Al-Attas proposes the integration of zakat as the main mechanism in replacing the conventional tax system, by highlighting the importance of Islamic ethical values, such as tauhid, amanah, and ihsan, in tax management. This study uses a qualitative method with a literature study approach. The results of this study indicate that the concept of tax according to al-Attas must be integrated with Islamic principles, because there are secular elements in the existing tax concept, so that tax can be a tool to achieve justice and community welfare.